The Localization of Long-Distance Dependency Components: Integrating the Focal-lesion and Neuroimaging Record - Piñango, Maria M.; Finn, Emily; Lacadie, Cheryl; Constable, R. Todd (Frontiers in Psychology, 2016)
In the sentence ``The captain who the sailor greeted is tall,'' the connection between the relative pronoun and the object position of greeted, represents a long-distance dependency (LDD), necessary for the interpretation of ``the captain'' as the individual being greeted. Whereas the lesion-based record shows preferential involvement of only the left inferior frontal (LIF) cortex, associated with Broca's aphasia, during real-time comprehension of LDDs, the neuroimaging record shows additional involvement of the left posterior superior temporal (LPST) and lower parietal cortices, which are associated with Wernicke's aphasia. We test the hypothesis that this localization incongruence emerges from an interaction of memory and linguistic constraints involved in the real-time implementation of these dependencies and which had not been previously isolated. Capitalizing on a long-standing psycholinguistic understanding of LDDs as the workings of an active filler, we distinguish two linguistically defined mechanisms : GAP-search, triggered by the retrieval of the relative pronoun, and GAP-completion, triggered by the retrieval of the embedded verb. Each mechanism is hypothesized to have distinct memory demands and given their distinct linguistic import, potentially distinct brain correlates. Using fMRI, we isolate the two mechanisms by analyzing their relevant sentential segments as separate events. We manipulate LDD-presence/absence and GAP-search type (direct/indirect) reflecting the presence/absence of intervening islands. Results show a direct GAP-search - LIF cortex correlation that crucially excludes the LPST cortex. Notably, indirect GAP-search recruitment is confined to supplementary-motor and lower-parietal cortex. GAP-completion instead shows recruitment implicating the dorsal pathway including: the supplementary motor cortex, left supramarginal cortex, precuneus, and anterior/dorsal cingulate. Altogether, the results are consistent with previous findings connecting GAP-search, as we define it, to the LIF cortex. They are not consistent with an involvement of the LPST cortex in any of the two mechanisms, and therefore support the view that the LPST cortex is not crucial to LDD implementation. Finally, results support neurocognitive architectures that involve the dorsal pathway in LDD resolution and that distinguish the memory commitments of the LIF cortex as sensitive to specific language-dependent constraints beyond phrase-structure building considerations.